The person in the civil degree. Critical to reality of the process of adoption and non-adoption of adolescents - Janeth Carolina Barrera Sandoval; Manuel Mauricio Moreno Villamizar (Via Inveniendi Et Iudicandi, 2018)
This article contains the results achieved within the research project whose objective was to investigate the process of adoption and non-adoption of adolescents in the Colombian Family Welfare Institute (icbf), in the department of Meta. One of the aims of the icbf is to lead and to deliver in adoption to the holders of rights violated; to find a family to achieve reestablishment of the rights of minors and provide family stability through a figure adoption, in a parent-child relationship between people who do not have it by nature. It also analyzes the monitoring and guarantees provided by the State through the icbf against adopted and non-adopted adolescents and all the factors that approach the problems of these teenagers in the social and cultural environment.